Convalescent plasma for COVID-19: A reasonable option for the pandemic based on both scientific and practical point of views - Mardiah Suci Hardianti; Syahru Agung Setiawan; David Dwi Putera; Teguh Triyono; Jarir At Thobari; Johan Kurnianda (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Convalescent plasma treatment has become a promising adjunctive option to treat COVID-19. Several case reports consistently supported the feasibility of this approach by showing the safety and improvements of clinical and laboratory aspects from the treated patients. However, more clinical trials are still required to establish the definitive statement about its potential effectiveness. We review the scientific basis for the application of convalescent plasma in COVID-19 to understand its potentials better. We also cover the potential risks and benefits for this treatment in order to be more selective and careful when preparing and deciding to apply this approach. Lastly, we summarize any important points to monitor after the administration of this treatment to prioritize safety and measure the effectiveness of the treatment.